The Roles of Mental Construal Level Theory in the Promotion of University Students' Pro-environmental Behaviors - Jia, Yanhui; Tian, Jie; Liu, Haiyue (Frontiers in Psychology, 2021)
Although green technological innovation is designed to combat climate change, recent research suggests that increased attention to technological innovations might decrease climate change risk perception and reduce pro-environmental behaviors due to the feeling of being assured, which is referred to as risk compensation behavior. Although there has been a growing interest in reducing the risk compensation effect related to climate change, the academic literature in this area is very limited. In this study, we propose a psychological intervention to mitigate a sample of university students’ (N=1500) irrational response to green technological innovation so as to promote their pro-environmental behaviours. Our experiments identify students’ mental construal level as an important psychological factor that, when combined with a proper message framing strategy of introducing new green technologies, can remedy their irrational response to new green technologies. Our findings suggest that highlighting the new technology as playing a preventive/promotional role related to climate change can mitigate risk compensation behaviour and eventually promote students’ pro-environmental behaviours when they are at a high/low mental construal level.